Pengaruh Emotional Content, Perceived Product Quality dan Perceived Empathy terhadap Purchase Decision Olive Fried Chicken di Glagahsari Yogyakarta - Ida Bagus Nyoman Udayana; Ade Yogi Ferawan (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to determine: (1) The positive effect of Emotional Content, the more Purchase Decision, (2) the effect of Perceived Product Quality on the increase in Purchase Decision, (3) the Effect of Perceived Empathy on the Increase of Purchase Decision. This research is a quantitative research, in sampling using purposive sampling technique. Questionnaires are used to collect data, with questionnaires distributed to respondents and then collected again. Data collection uses a questionnaire method that has been tested for validity and reliability. This study uses a sampling technique by distributing questionnaires to take a sample of 51 people so that they can be tested for validity and reliability. This study has several potential limitations for future research. First, the data collected in this study only focused on consumers who had purchased olive fried chicken in Yogyakarta. The data collected is quite limited because it is only shared with 51 people. Future research may consider collecting data on a larger scale. In addition, this study uses a survey to collect data. Our research findings show that Emotional Content, Perceived Product Quality and Perceived Empathy have a significant positive effect on Purchase Decision. Perceived Product Quality is the most influential variable on Purchase Decision. Keywords: Emotional Content, Perceived Product Quality, Perceived Empathy, Purchase Decision